HOUSEHOLD PREFERENCES FOR PROCUREMENT OF RICE CONSUMPTION IN MAKASSAR CITY, INDONESIA - Sulianderi, Ni Made Viantika; Tenriawaru, Andi Nixia; Darma, Rahim (Syarif Hidayatullah State Islamic University Jakarta, 2023)
Advances in technology in production, rice processing, and community welfare are changing consumer behavior. The purpose of the study is to analyze consumer preferences in rice procurement. This study was conducted in the city of Makassar, South Sulawesi Province with a survey method on 60 households of respondents who were randomly selected in three residential clusters, namely housing complexes, suburban areas, and the middle of the city. The data analyzed is based on the income level of the household. There are two groups of a factor in rice procurement, rice properties and buying methods. Rice properties consist of, characteristics, varieties, buying preferences, and packaging sizes. The buying process consists of methods, buyers, places, sellers, and information sources for rice procurement. The data is analyzed by using the descriptive method and presented on the frequency table matrix. The results showed that households buy rice with considerations, such as variety, price, and buying habits. While the purchase method is carried out either by the wife or husband, packaging 10-25 kg, and shopping at traditional markets and small groceries for low-income households. In contrast, supermarkets and small grocery places are chosen as places to shop for rice for high-income households. The source of information about the quality and price of rice is obtained at the place of purchase. The ease of obtaining rice is affected by packaging, place of purchase, and quality information are factors that must be considered in the development of rice marketing in the city.